Amateur boxing in the last 59 years. Impact of rules changes on the type of verdicts recorded and implications on boxers' health. Issue 7 (12th January 2013) - Bianco, Massimiliano; Loosemore, Mike; Daniele, Gianlorenzo; Palmieri, Vincenzo; Faina, Marcello; Zeppilli, Paolo
Abstract : Background/aim: Several changes have occurred in Olympic boxing (OB) in the last few decades, influencing the results in official competitions. The aim of this study was to assess how the evolution of rules changed the rate of the results that can influence boxers' health. Methods: From a web-research, the results of OB tournaments from 1952 to 2011 were reviewed (29 357 bouts). For each event, rate of knockout (KO), referee-stop contest (RSC), RSC-Head (RSCH), RSC-Injury (RSCI), RSC-Outclassed (RSCO), abandon, disqualification and points decisions were recorded. In our analysis we investigated the changes that occurred after the introduction of the standing-count rule (1964), mandatory head guard (1984), computerised scoring system (1992), RSCO (2000–2009) and modification of bout formula 3×3 min rounds (3×3, until 1997, 5×2 min rounds (5×2) until 1999, 4×2 min rounds (4×2) until 2008, 3×3 from 2009). Results: The most important results were: (1) an RSCI rate increase (0.72–2.42%, p<0.03) after the standing-count rule; (2) a lower RSCI (0.60%, p<0.001) and higher RSCH (1.31–4.92%, p<0.001) and RSC (9.71–13.05%, p<0.03) rate with mandatory head guard; (3) a KO rate reduction (6.44–2.09%, p<0.001) with the computerised scoring system; (4) an RSC (13.15–5.91%, p<0.05) and RSCH (4.23–1.41%, p<0.001) rate reduction comparing 5×2–4×2 bouts. Conclusions: In the last six decades, along with rule changes in OB, a clear reduction of health challenging results was observed. In the near future, older rules will be adopted (no head guard and a manual scoring system). Continued medical surveillance is important to ensure that new rule changes do not result in poor medical outcomes for the boxers.